Implementation of HIV Self-Testing to Reach Men in Rural uMkhanyakude, KwaZulu-Natal, South Africa. a DO-ART Trial Sub Study - Sithole, Nsika; Shahmanesh, Maryam; Koole, Olivier; Krows, Meighan; Schaafsma, Torin; Siedner, Mark J.; Celum, Connie; Barnabas, Ruanne V.; Shapiro, Adrienne E. (Frontiers in Public Health, 2021)
Background: KwaZulu–Natal, South Africa has one of the highest HIV prevalence rates globally. Persons <35 years and men have lower rates of HIV testing. HIV self-testing (HIVST) may overcome many barriers of facility-based HIV testing in order to identify HIV positive young persons and men and link them to care. We investigated whether HIVST distribution was a feasible approach to reach men and assessed the proportion of participants who reported their HIVST results, tested positive and linked to care. Methods: Teams comprised of a nurse, clinic research assistant, and recruiters distributed HIVST kits in rural uMkhanyakude, KwaZulu-Natal from August – November 2018 with a focus on testing men. Workplaces (farms), social venues, taxi ranks, and homesteads were used as HIVST distribution points following community sensitisation through community advisory boards and community leaders. HIVST kits, demonstration of use, and small incentives to report testing outcomes were provided. The Department of Health provided confirmatory testing and HIV care at clinics. Results: Over 11 weeks in late 2018, we distributed 2634 HIVST kits with 2113 (80%) kits distributed to persons aged < 35 years and 2,591 (98%) kits distributed to men with 356 (14%) first time testers. Of the HIVST distributed, 2,107 (80%) reported their results to the study team, and 157 (7%) tested positive. Of persons who tested positive, 107/130 (78%) reported having a confirmatory test of which 102/107 (95%) were positive and initiated on ART. No emergencies or social harms were reported. Conclusion: Large scale distribution of HIVST kits targeting men in rural KwaZulu-Natal is feasible and highly effective in reaching men, including those who had not previously tested for HIV. While two-thirds of persons who tested HIV positive initiated ART, additional linkage strategies are needed for those who do not link after HIVST. HIVST should be used as a tool to reach men in order to achieve 95% coverage in the UNAIDS testing and care cascade in KwaZulu-Natal.